MODEL GREEN CONSUMPTION DAN GREEN FINANCE DI 5-EMMA COUNTRIES - Hutasoit, Anita H (JEBIM Prima, 2024)
The importance of protecting the environment is increasing globally. Significant environmental losses worldwide have been caused by the decline of natural resources, climate change, worldwide population growth, and unsustainable consumption practices. Green consumption, also known as environmentally friendly consumption, has become a growing trend worldwide. To meet new consumer demands, companies must also make more environmentally friendly measures. The ARDL panel model is used in this research to understand how green consumption is controlled by the variables that have been included in this research. Auto Regressive Distribution Lag is a regression model that takes into account the long term and short term. The data used in this research is secondary data collected from the worldbank and ceic websites from 2015-2022. The research results show that the overall leading indicator, both long term and short term, is green finance. However, in the long term there are 4 variables that can control green consumption, namely Green finance, Green inflation, Purchasing power parity, and Green technology.